Using a large ensemble of simulations to assess the Northern Hemisphere stratospheric dynamical response to tropical volcanic eruptions and its uncertainty - Matthias Bittner; Hauke Schmidt; Claudia Timmreck; Frank Sienz (Geophysical Research Letters)
Abstract The observed strengthening of the Northern Hemisphere (NH) polar vortex after tropical volcanic eruptions appears to be underestimated by coupled climate models. However, there are only a limited number of observed eruptions, which makes the attribution of volcanic signals difficult, because the polar vortex is also influenced by other external forcing factors as well as internal variability. We show with a 100‐member ensemble of historical (1850–2005) simulations with the Max Planck Institute Earth System Model that an ensemble larger than what is provided by the Coupled Model Intercomparison Project Phase 5 (CMIP5) models is needed to detect a statistically significant NH polar vortex strengthening. The most robust signal can be found when only the two strongest eruptions (Krakatau and Pinatubo) are considered in contrast to including smaller eruptions to increase the sample size. For these two strongest eruptions, the mean of 15 CMIP5 models shows a statistically significant strengthening of the NH polar vortex as well.